Evaluation of β‐FeSi2/Si‐interface using Ag‐coating on Si surface. Issue 12 (4th November 2013) - Akiyama, Kensuke; Motomura, Shunichi; Hayashi, Gohei; Funakubo, Hiroshi; Itakura, Masaru; Maeda, Yoshihito; Suzuki, Motofumi
Abstract β‐FeSi2 films preferred to (100)‐, (010)/(001)‐ and (101)/(110)‐orientation on Ag‐coated Si(100), Ag‐coated Si(110) and Ag‐coated Si(111) substrates, respectively. The full width at half maximum of the rocking curve of the β‐FeSi2800, 040 /004 and 202 /220 for the (100)‐, (010)/(001)‐ and (101)/(110)‐oriented β‐FeSi2 films were 0.59°, 0.20° and 0.18°, indicating the good perfect quality of the crystal orientation. The photoluminescence intensity of the (101)/(110)‐orientated β‐FeSi2 films on Ag‐coated Si(111) substrates was larger than the others, when the samples were indirectly excited by Ar‐ion laser irradiation to the Si substrate side. The hetero‐interface constituted with the β‐FeSi2 (101)/(110) plane and Si(111) plane seems to have the lowest density of non‐radiative center. From the transmission electron microscope analysis, the hetero‐interface constituted with the β‐FeSi2 (101)/(110) plane and Si(111) plane is considered as thermodynamically stable. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)